Metabolomics Analysis Reveals Potential Mechanisms in Bupleurum L. (Apiaceae) Induced by Three Levels of Nitrogen Fertilization - Jialin Sun; Weinan Li; Ye Zhang; Yun Guo; Zejia Duan; Zhonghua Tang; Ann Abozeid (Agronomy, 2021)
Bupleurum (Apiaceae) is widely used in traditional Chinese medicine to treat inflammatory and infectious diseases. Although roots are the only used parts in China, other countries use the whole plant. The yield and quality of Bupleurum depend mainly on fertilizers, especially nitrogen. The current study aimed to assess the relationship between the nitrogen fertilization level and the quality and metabolomic response of different parts (flowers, main shoots, lateral shoots and roots) of Bupleurum to three nitrogen fertilization levels (control group: 0 kg·ha−1; low-nitrogen group: 55 kg·ha−1; high-nitrogen group: 110 kg·ha−1). The results showed that a high nitrogen level increases Bupleurum yield and quality parameters only in aerial parts, especially flowers, but has no significant effect on roots. The HPLC method was exploited for simultaneous quantification of three saikosaponins (A, C and D), which are the main bioactive components in the plant. It was found that the total content of saikosaponins decreased with high nitrogen fertilization in roots but significantly increased in flowers. Moreover, nitrogen fertilizer promoted the content of saikosaponin A but inhibited saikosaponins C and saikosaponins D in most parts of the plant. To study the response of primary metabolites, we adopted gas chromatography–mass spectrometry (GC−MS) analysis; 84 metabolites were identified that were mostly up-regulated with a high nitrogen level in flowers but down-regulated in roots. Four differential metabolites—D-fructose, lactose, ether and glycerol—were recognized as key metabolites in Bupleurum under nitrogen fertilization. Meanwhile, The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment results explained that the impact of nitrogen fertilization on Bupleurum was attributed to the C-metabolism, N-metabolism, and lipids metabolism. This research put forward new insights into potential mechanisms and the relationship between the quality and yield of Bupleurum and nitrogen fertilization.